Sikap Generasi Muda Terhadap Melukat Sebagai Perilaku Coping Berbasis Budaya Bali - Pandeirot, Gabriela Gebi Rosi (Publikasi Indonesia, 2025)
elukat is a spiritual cleansing ritual in Balinese culture, believed to alleviate emotional burdens and enhance psychological calmness. Amidst the dynamic challenges faced by today’s youth including academic stress, identity pressure, and shifting cultural values, this practice continues to be carried out with various adaptations. This study aims to explore the attitudes of young Balinese individuals toward melukat as a culturally rooted coping behavior. Using a qualitative phenomenological approach, data were collected through in-depth interviews and non-participant observation involving three participants aged 20–21 who had engaged in melukat at least twice in the past year. Thematic analysis was conducted based on the Miles and Huberman model. The findings reveal three attitude tendencies: (1) positive attitudes, in which melukat is seen as spiritually and psychologically beneficial and practiced reflectively to manage emotional stress; (2) positive attitudes with caution, reflecting openness to integrating melukat with professional help such as psychologists; and (3) negative attitudes, where melukat is perceived as not always effective or relevant in a psychological context. These findings suggest that young people do not entirely reject traditional practices but instead reconstruct their meaning in ways that are more adaptive to contemporary contexts.